The Application of Rhetoric and Ethics in Salim A. Fillah's Da'wah on Dr. Richard Lee's YouTube Content: A Conceptual Analysis - Maesaroh, Maesaroh; Satriah, Lilis (Universitas Wiralodra, 2024)
Abstract This study aims to analyze the application of rhetoric and da'wah ethics used by Salim A. Fillah in the YouTube content of Dr. Richard Lee. Da'wah in the digital era demands innovative and effective approaches, utilizing social media platforms to spread religious messages. Salim A. Fillah, a renowned dai, employs rich rhetoric and da'wah ethics rooted in Islamic values in conveying his messages. This study uses a qualitative approach with content analysis methods to evaluate Salim A. Fillah's da'wah video on November 22, 2023, on Dr. Richard Lee's YouTube channel. The research findings indicate that the application of rhetorical strategies such as ethos, pathos, and logos, along with da'wah ethics that respect the audience and promote tolerance values, can enhance the effectiveness of conveying da'wah messages. These findings provide important insights for dai and preachers in effectively utilizing digital media to deliver religious messages in an engaging and ethical manner. Keywords: Rhetoric, Da'wah Ethics, Salim A. Fillah, YouTube, Content Analysis, Digital Da'wah